2019
DOI: 10.1080/13697137.2019.1656184
|View full text |Cite
|
Sign up to set email alerts
|

The remains of the taboo: experiences, attitudes, and knowledge about menopause in the workplace

Abstract: Objectives: This study explored experiences of, attitudes to and knowledge about menopause in the workplace among participants from the UK to assess the extent to which the menopause remains a taboo in this context. Method: An online survey was distributed via TUC (Trades Union Congress, UK) networks and social media and was completed by 5399 respondents. Questions explored three key issues relating to menopause at work: respondents' own experiences of menopause transition; disclosure at work; and availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Apart from hot flushes, a UK study found that the most challenging symptoms were poor concentration, tiredness, poor memory, feeling low/depressed and reduced confidence [45]. Furthermore, where menopause is considered to be a taboo subject, lack of discussion about menopause at work and stigma about menopause add to the burden of symptoms for women [36,46,47]. Another UK study of women aged 50-55 found that those with severe symptoms had a higher chance of exiting employment or reducing their working hours [48].…”
Section: Impact On Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from hot flushes, a UK study found that the most challenging symptoms were poor concentration, tiredness, poor memory, feeling low/depressed and reduced confidence [45]. Furthermore, where menopause is considered to be a taboo subject, lack of discussion about menopause at work and stigma about menopause add to the burden of symptoms for women [36,46,47]. Another UK study of women aged 50-55 found that those with severe symptoms had a higher chance of exiting employment or reducing their working hours [48].…”
Section: Impact On Workmentioning
confidence: 99%
“…Strategies need to involve all in the workplace and to include occupational health professionals [12]. Women want increased knowledge and awareness in the workplace about the menopause so that it is no longer a taboo subject [46,47]. While some women may want to be able to talk about it and agree appropriate work adjustments, others may feel uncomfortable disclosing their menopause status to line managers and employers [45,46].…”
Section: Employers and The Menopausementioning
confidence: 99%
“…Beck et al . also observed that among British women hot flashes were the most commonly mentioned menopausal symptoms together with fatigue, night sweats and sleeplessness [ 38 ], which dominate the list of the most common menopausal ailments [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing presence of employed women undergoing menopause has stimulated a growing corpus of research. This research initially took a primarily medical perspective and has, more recently, incorporated a psychosocial perspective by highlighting the complex relationship between menopause and work [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, empirical evidence has also shed light on hindrances in the workplace that may undermine women’s well-being during menopausal age. Regardless of whether they are actually in menopause, older women (e.g., over 50) are at a higher risk of being subjected to social stigma and targeted for workplace discrimination due to their (supposed) menopausal status [ 7 , 16 ]. Negative stereotypes, which are culturally rooted in many workplaces, characterize menopausal women as irrational, emotionally unstable, and non-performative and may work as self-fulfilling prophecies [ 17 ], thus impeding women’s abilities to fully express their potential at work.…”
Section: Introductionmentioning
confidence: 99%